How Did the COVID-19 Pandemic Affect Trauma Volume at an Urban Level I Trauma Center?. Issue 4 (April 2022) - Hahn, Alexandra; Brown, Tommy; Chapman, Brett; Marr, Alan; Stuke, Lance; Greiffenstein, Patrick; Schoen, Jonathan; Hunt, John P.; Smith, Alison
Introduction: The COVID-19 pandemic changed the face of health care worldwide. While the impacts from this catastrophe are still being measured, it is important to understand how this pandemic impacted existing health care systems. As such, the objective of this study was to quantify its effects on trauma volume at an urban Level 1 trauma center in one of the earliest and most significantly affected US cities. Methods: A retrospective chart review of consecutive trauma patients admitted to a Level 1 trauma center from January 1, 2017 to December 31, 2020 was completed. The total trauma volume in the years prior to the pandemic (2017-2019) was compared to the volume in 2020. These data were then further stratified to compare quarterly volume across all 4 years. Results: A total of 4138 trauma patients were treated in the emergency room throughout 2020 with 4124 seen during 2019, 3774 during 2018, and 3505 during 2017 in the pre-COVID-19 time period. No significant difference in the volume of minor trauma or trauma transfers was observed ( P < .05). However, there was a significant increase in the number of major traumas in 2020 as compared to prior years (38.5% vs 35.6%, P < .01) and in the volume of penetrating trauma (29.1% vs 24.0%, P < .01). Discussion: During the COVID-19 outbreak, trauma remained a significant health care concern. This study found an increase in volume of penetrating trauma, specifically gunshot wounds throughout 2020. It remains important to continue to devote resources to trauma patients during the ongoing COVID-19 pandemic.